Contributions of university extension to the teacher training of students of the professorate. Experiences in Geography subject of the National University of Litoral - Lossio, Oscar (2023)
This article addresses the contributions of the university extension to the teacher training of students of the professorate. First, we will present reflections of the fifteen years of trajectory in its curricular inclusion, in the participation of projects, in university management and in research linked to extension. In second place, some propositions that we built from that trajectory with the analysis of what we already narrated, in a collective interview and in depth, will be articulated by three students that participated in 2019 in the experience of curricular inclusion of extension in the subject Didactics of Geography from the National University of Litoral (Argentina). One main premise is transversal to the entire work, and it refers to the relevance that recognising the theoretical, epistemological and polítical basis have for students, primarily for granting sense to their actions around the university substantive function, like enhancing the construction of learning about being a teacher in the interventions made in educational institutions. Because of that, we consider primordial inquiring, analyzing, and strengthening the practices of teaching and learning about those bases. In a particular way, and according to the first ones, we promote the construction of the specific field that is Didactics of university extension.